METODE TUGAS DAN RESITASI PADA MATERI GEJALA PEMANASAN GLOBAL UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI KELAS XI SMA NEGERI 5 PEKANBARU - Lestari, Yenni; Irianti, Mitri; Yennita, Yennita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study was aimed to determine the improvement of students’ cognitive learning outcomes by applying assignment and recitation method. This research was conducted at SMA Negeri 5 Pekanbaru from January to February 2018. Two groups of samples were choose from homogeneous classes. Quasi experiments in the form of intact group comparison was used in this study. The data was obatained from cognitive learning result test which consisted of 15 items of multiple choice. Descriptive and inferential analysis were used for data analysis. Based on descriptive analysis, the average of students’ absorption ability in the experimental class was 80,19% and 73,53% for control class, this indicated that the effectiveness of student learning in experiment class was higher than in the control class. Based on inferential analysis through independent sample t test sig value. (2-tailed) = 0.026 < 0.05 was obatained. This mean that there was a significant increase in students’ learning result. Thus it can be concluded that the use of assigment and resitation method can enhance student’s learning outcomes in XI class SMA Negeri 5 Pekanbaru on indication of global warming material.Keywords : assignment and recitation method, cognitive learning outcomes, global warming material